Detection and evolutionary dynamics of somatic FAS variants in autoimmune lymphoproliferative syndrome: Diagnostic implications - Batlle-Masó, Laura; Garcia-Prat, Marina; Parra-Martínez, Alba; Franco-Jarava, Clara; Aguiló-Cucurull, Aina; Velasco, Pablo; Antolín, María; Rivière, Jacques G.; Martín-Nalda, Andrea; Soler-Palacín, Pere; Martínez-Gallo, Mónica; Colobran, Roger (Frontiers in Immunology, 2022)
Autoimmune lymphoproliferative syndrome (ALPS) is a rare primary immune disorder characterized by impaired apoptotic homeostasis. The clinical characteristics include lymphoproliferation, autoimmunity (mainly cytopenia), and an increased risk of lymphoma. A distinctive biological feature is accumulation (>2.5%) of an abnormal cell subset composed of TCRαβ+ CD4-CD8- T cells (DNTs). The most common genetic causes of ALPS are monoallelic pathogenic variants in the FAS gene followed by somatic FAS variants, mainly restricted to DNTs. Identification of somatic FAS variants has been typically addressed by Sanger sequencing in isolated DNTs. However, this approach can be costly and technically challenging, and may not be successful in patients with normal DNT counts receiving immunosuppressive treatment. In this study, we identified a novel somatic mutation in FAS (c.718_719insGTCG) by Sanger sequencing on purified CD3+ cells. We then followed the evolutionary dynamics of the variant along time with an NGS-based approach involving deep amplicon sequencing (DAS) at high coverage (20,000-30,000x). Over five years of clinical follow-up, we obtained six blood samples for molecular study from the pre-treatment (DNTs>7%) and treatment (DNTs<2%) periods. DAS enabled detection of the somatic variant in all samples, even the one obtained after five years of immunosuppressive treatment (DNTs: 0.89%). The variant allele frequency (VAF) range was 4%-5% in pre-treatment samples and <1.5% in treatment samples, and there was a strong positive correlation between DNT counts and VAF (Pearson’s R: 0.98, p=0.0003). We then explored whether the same approach could be used in a discovery setting. In the last follow-up sample (DNT: 0.89%) we performed somatic variant calling on the FAS exon 9 DAS data from whole blood and purified CD3+ cells using VarScan 2. The c.718_719insGTCG variant was identified in both samples and showed the highest VAF (0.67% blood, 1.58% CD3+ cells) among >400 variants called. In summary, our study illustrates the evolutionary dynamics of a somatic FAS mutation before and during immunosuppressive treatment. The results show that pathogenic somatic FAS variants can be identified with the use of DAS in whole blood of ALPS patients regardless of their DNT counts.